Perancangan Aplikasi Penyedia Jasa Ilustrator berbasis Android menggunakan Metode Human Centered Design (HCD) - Nooriza Fariha Rumagutawan; Agi Putra Kharisma; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
An illustrator is an artist who specializes in improving writing or explaining concepts by providing a visual representation that matches the content of the text or related ideas (Charles & Herbert, 1985). In 2018 the Indonesian Information and Communication Technology Creative Industry Society (MIKTI) stated that the most popular startup was e-commerce with 352 startups. This opens up job opportunities for illustrators and attracts illustrators who want to pursue this work, unfortunately being a freelance illustrator in Indonesia is still difficult, because there is no special platform in Indonesia that connects illustrators and customers. Currently, freelance illustrators in Indonesia use illustrator marketplace services from abroad, their weakness is they do not provide withdrawals via bank or e-wallet, this causes a long process. In addition, selling illustrator services on social media is not the best solution, fraud often occurs from both parties. In order for the creative industry ecosystem to become stronger, a connector is needed which is none other than Information and Communication Technology (Anastasia & Handriani, 2018). The method used in this research is the Human Centered Design (HCD) method because this method focuses on solving problems creatively by focusing on consumer behavior and needs rather than their demographics. The test used in this research is usability testing using the System Usability Scale (SUS) questionnaire, This test produces an average value of 76.5, which means that the value is above the minimum average value of 68. The average value is between the ranges of good and excellent, including in grade B and acceptable to users (ACCEPTABLE).